2017
DOI: 10.3389/fmicb.2017.00855
|View full text |Cite
|
Sign up to set email alerts
|

A Thiazole Orange Derivative Targeting the Bacterial Protein FtsZ Shows Potent Antibacterial Activity

Abstract: The prevalence of multidrug resistance among clinically significant bacteria calls for the urgent development of new antibiotics with novel mechanisms of action. In this study, a new small molecule exhibiting excellent inhibition of bacterial cell division with potent antibacterial activity was discovered through cell-based screening. The compound exhibits a broad spectrum of bactericidal activity, including the methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus and NDM-1 Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Interestingly, tiplaxtinin also exhibits potent antibacterial activity against drug-resistant strains such as MRSA and vancomycinresistant E. faecium ATCC 700221. By means of a light scattering assay, the authors determined that this indole derivative enhances FtsZ polymerization in a concentration-dependent manner, a result that is in agreement with that of other FtsZ-targeting compounds already reported [52]. Finally, a The indole oxoacetic derivative tiplaxtinin (62, Figure 12) is a human plasminogen activator inhibitor (PAI-1) indicated in the treatment of acute arterial thrombosis [70].…”
Section: Quinazolinessupporting
confidence: 74%
“…Interestingly, tiplaxtinin also exhibits potent antibacterial activity against drug-resistant strains such as MRSA and vancomycinresistant E. faecium ATCC 700221. By means of a light scattering assay, the authors determined that this indole derivative enhances FtsZ polymerization in a concentration-dependent manner, a result that is in agreement with that of other FtsZ-targeting compounds already reported [52]. Finally, a The indole oxoacetic derivative tiplaxtinin (62, Figure 12) is a human plasminogen activator inhibitor (PAI-1) indicated in the treatment of acute arterial thrombosis [70].…”
Section: Quinazolinessupporting
confidence: 74%
“…In addition, it appears to restore the sensitivity of MRSA to methicillin and to be devoid of toxicity on mammalian cells and human erythrocytes. I20 [50] and its p-hydroxy analogue I21 [51] further reduce the activity gap between Gram-positive and Gram-negative strains, with MICs as low as 6 µM on E. coli (including a MDR strain) and 12 µM on MDR P. aeruginosa ( Table 8). The predicted binding mode on S. aureus FtsZ involves docking in the interdomain cleft, with a network of hydrophobic and ionic interactions.…”
Section: Berberine Analogues and Related Quinolinium Compoundsmentioning
confidence: 99%
“…quinolin-1-ium iodide derivative [105,106]. The results revealed that these compounds possess potent antibacterial activity against bacterial strains including MRSA and VRE.…”
Section: Based On the Above-mentioned Study Of Quinoline Derivativesmentioning
confidence: 99%
“…The results revealed that these compounds possess potent antibacterial activity against bacterial strains including MRSA and VRE. The results of biological study suggested that these compounds disrupt the dynamic assembly of FtsZ protein and Z-ring formation through inhibiting GTPase activity of FtsZ [105,106].…”
Section: Based On the Above-mentioned Study Of Quinoline Derivativesmentioning
confidence: 99%